Pesticide Storage: Keep It in the Container - Fred Fishel (EDIS, 2015)
Accidents happen quickly, and so do accidents with pesticides. Anyone storing pesticides, especially in the presence of children, needs to take precautions by keeping them in their proper, original containers. Several people have died when they unknowingly drank pesticides from containers that originally held soda, other beverages, or foodstuffs. In particular, the herbicide paraquat is highly toxic to humans; one small accidental sip can be fatal, and there is no antidote. This 3-page fact sheet was written by Fred Fishel, and published by the UF Department of Agronomy, May 2015. (Photo: Fred Fishel)